Overall survival in mCPRC patients treated with Radium-223 in association with bone health agents: a national multicenter study. (1st December 2020) - Frantellizzi, Viviana; Monari, Fabio; Mascia, Manlio; Costa, Renato; Rubini, Giuseppe; Spanu, Angela; Farcomeni, Alessio; Lodi Rizzini, Elisa; Cindolo, Luca; Licari, Maria; Lavelli, Valentina; Nuvoli, Susanna; et al.
Abstract: Purpose: Radium-223 has demonstrated efficacy in improving overall survival (OS) and in delaying symptomatic skeletal-related events (SREs). Bone Health Agents (BHA), i.e. RANK ligand inhibitor (Denosumab) and bisphosphonate such as zoledronic acid, are indicated to prevent SREs without a clear survival benefit. SREs on patient health have a high impact and it is, therefore, important to consider the role of new therapies with BHA to better understand the involvement of combination therapy. The primary aim of this multicentric study is to assess OS in mCRPC patients treated with Radium-223 in combination with BHA. Materials and methods: 430 consecutive patients treated with Radium-223 alone or in combination with BHA, affected by mCRPC, from January 2015 to July 2019 in six Italian Nuclear Medicine Units, were included. Furthermore, data were collected at baseline, after every Radium-223 administration, and during follow-up, at 3 and 6 months and 1 year after the 6th cycle. Clinical data have been evaluated before starting treatment with Radium-223 and at the end of treatment and/or at progression. Patients who received target bone therapy with BHA before Radium-223 treatment together with patients who did not receive this therapy at all (NO BHA GROUP), were compared to patients treated with concomitant Radium-223 and BHA (BHA GROUP). Results: In univariate models ( p  < .05) several clinical aspects have an impact on OS: concomitant BHA ( p  = .018), BMI ( p .001), ECOG PS ( p  = .000), Baseline Hb ( p  = .000), Baseline PSA ( p  = .000), Baseline tALP ( p  = .000), Baseline LDH ( p  = .000), and Baseline neutrophils ( p  = .009). Baseline Hb, Baseline tALP, and Baseline LDH have been confirmed as statistically significant parameters in multivariate models. Indeed, concomitant BHA has not a significant impact on OS ( p  = .244) in multivariate models. Conclusions: At univariate analysis, our data showed that NO BHA GROUP and BHA GROUP differ in OS by 7 months (95%CI: (1–16.4), p  = .02). This is not confirmed at multivariate analysis where after adjusting for other baseline factors, BHA is not significant anymore. This is clearly explained as bias by indication: patients with the same levels of tALP, Hb, and LDH receiving or not receiving BHA are expected to have a similar survival. Our results support and confirm the role of Radium-223 therapy on OS and, furthermore, appear to confirm that BHA treatment has not a survival benefit.